Evaluation of Skull Cortical Thickness Changes With Age and Sex From Computed Tomography Scans. (8th September 2015) - Lillie, Elizabeth M; Urban, Jillian E; Lynch, Sarah K; Weaver, Ashley A; Stitzel, Joel D
ABSTRACT: Head injuries resulting from motor vehicle crashes (MVC) are extremely common, yet the details of the mechanism of injury remain to be well characterized. Skull deformation is believed to be a contributing factor to some types of traumatic brain injury (TBI). Understanding biomechanical contributors to skull deformation would provide further insight into the mechanism of head injury resulting from blunt trauma. In particular, skull thickness is thought be a very important factor governing deformation of the skull and its propensity for fracture. Previously, age‐ and sex‐based skull cortical thickness changes were difficult to evaluate based on the need for cadaveric skulls. In this cross‐sectional study, skull thickness changes with age and sex have been evaluated at homologous locations using a validated cortical density‐based algorithm to accurately quantify cortical thickness from 123 high‐resolution clinical computed tomography (CT) scans. The flat bones of the skull have a sandwich structure; therefore, skull thickness was evaluated for the inner and outer tables as well the full thickness. General trends indicated an increase in the full skull thickness, mostly attributed to an increase in the thickness of the diploic layer; however, these trends were not found to be statistically significant. There was a significant relationship between cortical thinning and age for both tables of the frontal, occipital, and parietal bones ranging between a 36% and 60% decrease from ages 20 to 100 years in females, whereas males exhibited no significant changes. Understanding how cortical and full skull thickness changes with age from a wide range of subjects can have implications in improving the biofidelity of age‐ and sex‐specific finite element models and therefore aid in the prediction and understanding of TBI from impact and blast injuries. © 2015 American Society for Bone and Mineral Research.